Wealth stratification in the early school career in Germany. (June 2020) - Dräger, Jascha; Müller, Nora
Highlights: Children of wealthy parents show higher math competences in the first grade. Competence differences by parental wealth remain stable throughout primary school. Children of wealthy parents are more likely to attend the highest school track. Wealth differences add to other social disparities by SES. Abstract: Recent research has established parental wealth as an important determinant of children's educational achievement. However, parental wealth is often ignored in research on social inequality in education, or its influence is only considered at later stages of children's educational careers. Our paper contributes to this research by examining the relationship between parental wealth and (1) children's math competences at the beginning of primary school; (2) the development of children's competences throughout primary school; and (3) children's transition from primary to secondary school. We are looking at Germany, where the early ability tracking may make an early investment in education particularly important. Analyzing data from the German National Educational Panel Study, we find that parental wealth has a distinct association with children's educational outcomes that adds to social disparities by other measures of parents' socioeconomic status (SES). Our results indicate that children in wealthy households have higher competences already in the first grade. This advantage remains stable throughout primary school and translates into a higher probability to attend the highest secondary school track. Moreover, children in these wealthy households are more likely to attend the highest secondary school track, net of differences in competences and performance. Our results imply that ignoring wealth as a component of parental SES leads to an underestimation of the level of social inequality in education in Germany.